How do College Students in India Respond to Gender-Based Violence (GBV)? - Asher Stephanie; Nagaraj Nitasha; Vyas Amita (Journal of Public Health International, 2020)
Rates of gender-based violence remain high during college in India, a time of adolescent malleability where gender norms, gender perspectives, and responses to violence are open to change. Few gender-based violence interventions focus on college students and even fewer on bystander intervention as a preventative approach - a concept novel to India. This cross-sectional study reached 603 college students in India to examine current gender norms and perspectives, bystander intervention behaviours, and discussion of gender-based violence on campuses. Statistically significant differences were found between male and female college students in all scenarios of bystander intervention response and frequency of discussion of gender-based violence. Multinomial logistic regression analysis showed significant differences in those who had never seen violence or had a positive bystander intervention response, compared to those who responded negatively. Given the findings, targeting college students appears a promising approach to change the narrative of gender-based violence and norms in India.
Keywords: Gender